Observed & Experiential Integration (OEI) Therapy for Adolescent Girls with Depression - Umi Nur Kholifah; Konto Iskandar Dinata (‎‎‎TAZKIYA Journal of Psychology, 2023)
Depression is a significant concern among female adolescents, necessitating effective therapeutic interventions. This study investigates the efficacy of Observed Experiential Integration (OEI) therapy in reducing depression levels among female adolescents. The research involves site selection, securing permissions, adapting measurement tools (BDI-II), modifying the OEI module, and selecting qualified therapists and observers. After implementing informed consent procedures, initial BDI-II assessments were conducted, followed by OEI therapy sessions. One week later, post-treatment assessments and a follow-up were used to evaluate the outcomes. This study employed a mixed-methods quantitative research approach with a quasi-single experimental design with pretest experimental and control groups, as well as posttest design, which is used to evaluate the effect of a treatment on a single case. Findings reveal notable reductions in depression levels post-OEI therapy. For instance, subject AIN's score decreased from 28 (moderate depression) in the pretest to 7 (minimal) in the follow-up. Subject LA's score dropped from 27 (moderate) in the pretest to 5 (minimal) in the follow-up. These results demonstrate the therapy's effectiveness in alleviating depression among female adolescents. This research provides valuable insights into the potential of OEI therapy as an effective intervention for adolescent female depression. However, limitations, including the small sample size, should be considered. Future research should explore broader populations and extended therapy durations. In conclusion, OEI therapy holds promise as a means of reducing depression among female adolescents and warrants further investigation.